A Deconstruction of Rural Governance Policy to Drive Local Economies - Ahmad Iman Sukri; Kusumastuti, Retno; Achmad Lutfi (Journal of Sustainable Development and Regulatory Issues (JSDERI), 2025)
Rural governance policies play a critical role in determining the trajectory of local economic development, particularly in marginalized or agrarian regions. However, in practice, the centralistic and technocratic approach still dominates, positioning villages as policy implementers rather than locally based policy designers. This article examines the structure of village governance policy in Indonesia and its impact on local economic development through a deconstruction approach. Through a case study of Panggungharjo Village in Yogyakarta, this research analyzes how local actors successfully transformed village governance by dismantling the political, administrative, and policymaking frameworks. This research uses a socio-legal method with a discourse analysis approach to uncover power relations, participatory practices, and institutional innovations at the village level. This research compares village governance in India’s Panchayati Raj and Germany’s federal system to enrich the analysis. The research findings indicate that, firstly, the village governance structure in Indonesia is still dominated by a hierarchical and technocratic administrative approach, which limits the space for village initiatives in designing development based on local needs. Second, the village governance models in India and Germany offer valuable lessons for Indonesia, with India excelling in citizen political participation and Germany excelling in bureaucratic efficiency and technology-based public services. The combination of strong community engagement and institutional capacity building is crucial for building inclusive, adaptive, and sustainable village governance in Indonesia. Third, the ideal model of good village government governance is supported by strong leadership, adequate institutional capacity, and high public trust in the governance process.